Frontostriatal Mechanisms in Instruction-Based Learning as a Hallmark of Flexible Goal-Directed Behavior - Wolfensteller, Uta; Ruge, Hannes (Frontiers in Psychology, 2012)
The present review intends to provide a neuroscientific perspective on the flexible (here: almost instantaneous) adoption of novel goal-directed behaviors. The overarching goal is to sketch the emerging framework for examining instruction-based learning and how this can be related to more established research approaches to instrumental learning and goal-directed action. We particularly focus on the contribution of frontal and striatal brain regions drawing on studies in both, animals and humans, but with an emphasize put on human neuroimaging studies. In section one, we review and integrate a selection of previous studies that are suited to generally delineate the neural underpinnings of goal-directed action as opposed to more stimulus-based (i.e., habitual) action. Building on that the second section focuses more directly on the flexibility to rapidly implement novel behavioral rules as a hallmark of goal-directed action with a special emphasis on instructed rules. In essence, the current neuroscientific evidence suggests that the prefrontal cortex and associative striatum are able to selectively and transiently code the currently relevant relationship between stimuli, actions, and the effects of these actions in both, instruction-based learning as well as in trial-and-error learning. The premotor cortex in turns seems to form more durable associations between stimuli and actions or stimuli, actions and effects (but not incentive values) thus representing the available action possibilities. Together, the central message of the present review is that instruction-based learning should be understood as a prime example of goal-directed action, necessitating a closer interlacing with basic mechanisms of goal-directed action on a more general level.